Analysis of Mouse Growth Plate Development. Issue 1 (1st March 2016) - Mangiavini, Laura; Merceron, Christophe; Schipani, Ernestina
Abstract: To investigate skeletal development, pathophysiological mechanisms of cartilage and bone disease, and eventually assess innovative treatments, the mouse is a very important resource. During embryonic development, mesenchymal condensations are formed, and cells within these mesenchymal condensations either directly differentiate into osteoblasts and give origin to intramembranous bone, or differentiate into chondrocytes and form a cartilaginous anlage. The cartilaginous anlage or fetal growth plate is then replaced with bone. This process is also called endochondral bone development, and it is responsible for the generation of most of our skeleton. Here we discuss in detail the most common in vivo and in vitro techniques our laboratory is currently using for the analysis of the mouse fetal growth plate during development. © 2016 by John Wiley & Sons, Inc.